A new method of assessing the surgical margin in rectal carcinoma—using nonlinear optical microscopy. (5th May 2016) - Li, Lianhuang; Chen, Zhifen; Kang, Deyong; Deng, Tongxin; Jiang, Liwei; Zhou, Yi; Liu, Xing; Jiang, Weizhong; Zhuo, Shuangmu; Guan, Guoxian; Chi, Pan; Chen, Jianxin
Abstract: Nowadays, surgical resection is still the most effective treatment strategy for rectal carcinoma and one of the most important factors affecting whether the operation is successful or not is the surgical margin determination, especially in the distal rectal carcinoma which should take the sphincter-preserving issue into consideration. However, until recently no reliable evaluation method has been developed for this purpose. There are some shortcomings in intraoperative negative surgical margin assessment such as either lack of enough detailed information of biological tissues or the fact that it is time-consuming. Multiphoton microscopy (MPM)—nonlinear optical microscopy, which is based on the nonlinear optical process two-photon excited fluorescence (TPEF) and second harmonic generation (SHG), has the ability to label freely and noninvasively visualize tissue micro-architecture at the sub-cellular level. The advantage of providing high contrast and high resolution biomedical image in real time makes MPM have a wide range of applications in life sciences. In this study, we introduced MPM to identify the boundary between normal and abnormal rectal tissues. MPM images clearly exhibit biological tissue microstructure and its morphological changes in the regions of our interest, which enable it to determine the surgical margin in rectal carcinoma. It can be foreseen that once MPM imaging system is used in clinical examination, it will greatly improve the accuracy of surgical resection.